Downhole logging data from Nussloch loess cores - Denis-Didier Rousseau; Pierre Antoine; Philippe Adrien Pezard; Gilles Henry; Laurent Augustin; Alain De Moya; Olivier Moine; Luigi Ardito; Manfred Löscher; Frédéric Le Moal (PANGAEA, 2025)
The Nussloch Drilling Campaign (NUSS) involved drilling three loess sediment cores (85 mm in diameter) on April 21-25, 2019, on top of a loess hill at 49.31°N, 8.73°E, at an altitude of 215 m, close to the most recently described outcrop at the Nussloch reference site in Germany. Downhole logging was performed in the three drilling holes. This investigation aimed to conduct a comprehensive coring to acquire a sedimentary archive and perform logging measurements using Gamma Ray technology. The goal was to ensure the preservation of this distinctive Nussloch record for future research projects. Measurements of natural gamma radioactivity (gamma ray, GR) in counts per second (cps) were conducted in situ using an Antares spectral gamma slimline sonde. These results are expressed in terms of shale volume (Vsh). Vsh represents the fraction or percentage of the bulk rock volume that is composed of shale or clay minerals. This fraction is in most cases derived from downhole geophysical measurements of the natural gamma radioactivity of the penetrated formation. The measurements of natural gamma radioactivity (Gamma Ray - GR) in counts per second (cps). Vsh is computed choosing traditionally from logs and core data both a minimum and maximum value for clay content. These values are often denoted as GRmin for the host formation without clay, and GRmax when the formation is entirely made of clays, yielding a first order linear model with : Vsh = (GR- GRmin) / (GRmax-GRmin). To derive an estimate for clay content Vsh, these GR boundaries were chosen as 150 and 950 cps, respectively.